A Factor Analytical Method to Interactive Effects Dynamic Panel Models with or without Unit Root - Joakim Westerlund; Milda Norkute (Lund University, School of Economics and Management, Department of Economics, 2014)
In a recent study, Bai (Fixed-Effects Dynamic Panel Models, A Factor Analytical Method. Econometrica 81, 285-314, 2013a) proposes a new factor analytic (FA) method to the estimation of dynamic panel data models, which has the unique and very useful property that it is completely bias-free. However, while certainly appealing, it is restricted to fixed effects models without a unit root. In many situations of practical relevance this is a rather restrictive consideration. The purpose of the current study is therefore to extend the FA approach to cover models with multiple interactive effects and a possible unit root.
Keywords: C12; C13; C33; C36; 330; Interactive fixed effects; Dynamic panel data models; Unit root; Factor analytical method